Analisis Hukum Islam Terhadap Status Nasab Anak Akibat Married By Accident Dalam Film Dua Garis Biru - Hayatun Nufus; Musyaffa Amin Ash-Shabah; Suprihatin; Agus Supriyanto; Shabah, Musyaffa (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
Abtrack: This study aims to analyze Islamic law's perspective on the phenomenon of marriage by accident, as highlighted in the film "Dua Garis Biru," specifically regarding the child's lineage status and its impact. The method used is library research with a qualitative approach. The results of the study indicate that marriage resulting from an out-of-wedlock pregnancy raises complex issues in determining the child's lineage. In Islamic law, lineage is very important because it is related to children's civil rights such as inheritance, guardianship, and maintenance. The majority of Islamic scholars believe that children born from an out-of-wedlock relationship do not have lineage with the biological father unless the marriage took place before the pregnancy or the child was born at least six months after the marriage contract. In the film "Dua Garis Biru," the couple Dara and Bima married after Dara learned she was pregnant, but the gestational age before the marriage did not meet the minimum requirements for determining paternity. This indicates the unclear status of the child's lineage from an Islamic sharia perspective. This study emphasizes the importance of a deep understanding of Islamic law in dealing with cases of marriage by accident, so that children's rights remain protected even though positive law in Indonesia, through the Compilation of Islamic Law, permits the marriage of pregnant women without waiting for birth.   Keywords:  Lineage, Married By Accident, Islamic Law, Two Blue Lines, Illegitimate Children